CFD-study of the H-Rotor Darrius wind turbine performance in drag-lift and lift regime : Impact of type, thickness and chord length of blades - Ghiasi, Pedram; Najafi, Gholamhassan; Ghobadian, Barat; Jafari, Ali; Rizalman, Mamat; Mohd Fairusham, Ghazali (Elsevier B.V., 2023)
The high power coefficient of the Darrius vertical axis wind turbine lift regime has prompted researchers to concentrate their efforts on this regime, despite the fact that these turbines suffer from major problems in the drag-lift regime. In the present study, in addition to exploring the performance of the Darrius type wind turbine at blade tip speeds Ratio above 1, the effect of design factors on its performance at TSRs below 1 is also investigated. The results were extracted from numerical analysis recruiting Fluent software and the k-w SST turbulence model. The effect of blade type, thickness, and chord length on turbine performance has been investigated. The blade angle of attack (AOA) at TSR less than one was calculated using a new equation, and the results were evaluated. The numerical study of the Darrius wind turbine showed that increasing the chord length for symmetric and asymmetric airfoils from 0.1 to 0.2 m enhances the turbine performance in drag-lift regime, whereas decreasing chord length improves turbine performance at higher TSRs. The blade with a curvature of 4 % and a chord length of 0.1 m has the best performance at TSR 2.25. Increasing the thickness from 18 to 22 % of chord length exerts a negative influence on the turbine's performance in both regimes, and at lower TSRs, NACA0018 airfoil with a chord length of 0.2 m was of the optimum performance in the drag-lift regime.